Merchant Cultures - Antunes, Cátia, author.
1 online resource.
Keywords: Hans Holbein's Triumphs (1532-1534), commissioned for the headquarters of the Hanseatic League in London and Kano Naizen's The Portuguese namban ('foreigners') painted in 1543 in Japan are representations of worlds of trade, where wealth, speculation, exploitation, poverty, curiosity, encounters and the exotic relate effortlessly. These worlds multiplied in Africa, the America's, Asia and Europe as mercantile cultures met in a globalizing world. From these encounters, power, subjugation and conflict arose as part of the same world as cooperation, cross-culturalism and cosmopolitism. Understanding early modern merchant cultures is thus paramount to comprehend the sinews of globalization before 1800. Merchants worldwide shared trading interests. These interests shaped a panoply of encounters of mercantile cultures across space and time. This book sketches the commonalities and underlines the differences of mercantile practices and representations during the Early Modern period. Contributors are: Laurence Fontaine, David Graizbord, William Pettigrew, Edmond J. Smith, Radhika Seshan, Rila Mukherjee, Jurre J. A. Knoest, Noelle Richardson, Joseph P. McDermott, Mark Harberlëin, Francisco Bethencourt, Edgar Pereira, and Germano Maifreda.